2019
DOI: 10.3390/molecules24071328
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Dihydrocitrinone with Native and Chemically Modified Cyclodextrins

Abstract: Citrinin (CIT) is a nephrotoxic mycotoxin produced by Aspergillus, Penicillium, and Monascus genera. It appears as a contaminant in grains, fruits, and spices. After oral exposure to CIT, its major urinary metabolite, dihydrocitrinone (DHC) is formed, which can be detected in human urine and blood samples. Cyclodextrins (CDs) are ring-shaped molecules built up from glucose units. CDs can form host-guest type complexes with several compounds, including mycotoxins. In this study, the complex formation of DHC wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Cyclodextrins have been widely used to increase the performance and sensitivity of analytical techniques, including mycotoxin analysis [32,33,46]. Previous studies demonstrated that the fluorescence intensity of fluorescent mycotoxins can be strongly increased as a result of the formation of mycotoxin–CD host–guest type complexes [29,33,42,47]. It can be explained by the fact that water molecules can significantly quench the fluorescence of aromatic fluorophores [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclodextrins have been widely used to increase the performance and sensitivity of analytical techniques, including mycotoxin analysis [32,33,46]. Previous studies demonstrated that the fluorescence intensity of fluorescent mycotoxins can be strongly increased as a result of the formation of mycotoxin–CD host–guest type complexes [29,33,42,47]. It can be explained by the fact that water molecules can significantly quench the fluorescence of aromatic fluorophores [48].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular modeling studies have been performed at semi-empirical AM1 level using HyperChem 8 code [41,42]. After geometry optimization at AM1 level, the vibrational-rotational analyses were performed in harmonic approximation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ether type oxygen and polar hydrogen groups (C3 and C5) are present inside the trunk of the CDs. While the external hydroxyls are responsible for the relative solubility of CDs in water and micro-heterogeneous environments, the glycosidic oxygen bridges and, consequently, their pairs of non-binding electrons facing the interior of the cavity give this region, in addition to its Lewis basic character, hydrophobicity [18,19], making it capable of complexing nonpolar molecules [20]. The chirality caused by the five chiral carbons of the D-glucose unit associated with the rigidity of the macrocycle due to the intramolecular hydrogen interactions between the 2-and 3-hydroxyl groups are fundamental characteristics of the chemistry of CDs.…”
Section: General Characteristics Of Cyclodextrinsmentioning
confidence: 99%
“…After 10 ps MD simulation to equilibrate the system at room-temperature at MM+ level, the calculations for the complexes and the separated species interacted were performed at MINDO/3 level. To reduce the huge computational time, the random-methylated CD derivative (RAMEB, which have electron-rich cavity) was considered as negatively charged species of the native BCD [48,49].…”
Section: Modeling Studiesmentioning
confidence: 99%